2012
DOI: 10.1177/147323001204000236
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hippocampal Volume Measured Using Magnetic Resonance Imaging in Alzheimer's Disease, Vascular Dementia, Mild Cognitive Impairment and Pseudodementia

Abstract: Measurement of hippocampal volume may facilitate differentiation between dementia subtypes. There was a relationship between reduced hippocampal volume and the degree of cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Additionally, we found no significant differences in the swimming speed between the CI + Aβ‐operated rats and sham‐operated rats, suggesting that the CI + Aβ‐operated rats had cognitive dysfunction without disturbance of mobility. Dementia patients have atrophy and apoptosis of the hippocampus . The CI + Aβ‐operated rats also had neuron loss in the hippocampal CA1 region, and had an increase in caspase‐3 and cleaved caspase‐3 protein expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we found no significant differences in the swimming speed between the CI + Aβ‐operated rats and sham‐operated rats, suggesting that the CI + Aβ‐operated rats had cognitive dysfunction without disturbance of mobility. Dementia patients have atrophy and apoptosis of the hippocampus . The CI + Aβ‐operated rats also had neuron loss in the hippocampal CA1 region, and had an increase in caspase‐3 and cleaved caspase‐3 protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…A magnetic resonance imaging study has reported the structural–functional relationship between memory loss and hippocampal damage in patients with Alzheimer's dementia and cerebrovascular dementia ; these patients had atrophy of the hippocampus induced by neuronal death. In addition, β‐amyloid 1‐42 (Aβ1‐42)‐exposed neuronal culture and transient forebrain ischemia have cell death induced by apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal volumetry helps to differentiate Alzheimer's disease from mild cognitive impairment, and dementia from pseudodementia. It has been reported that hippocampal volumetry can also differentiate various types of dementias when used in combination with clinical and other supportive laboratory data [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…[1011] Although automatic method is faster and less likely to be affected by rater bias, manual measurements are considered gold standards. [12]…”
Section: Discussionmentioning
confidence: 99%
“…[4] Also, the data on hippocampal volumes are known in children,[5] young[6] and older adults[7] in India now. Hippocampal volumetry is useful in discriminating not only cognitively normal individuals from those with dementia[8] but can also differentiate MCI[9101112] from various types of dementias. [13141516] Visual rating of medial temporal lobes has been shown to have good sensitivity and specificity in the diagnostic evaluation in a preliminary study of Asian patients.…”
Section: Introductionmentioning
confidence: 99%